Impure poetry. About the edition of Clemente Rebora's works (Prassi Ecdotiche della Modernità Letteraria, 2017)
The essay deals with many problems and difficulties that editors have encountered while working at the volume Poesie, prose e traduzioni by Clemente Rebora. The most outstanding has been to distinguish between literary texts and other kind of writings that previous editions of Poesie (Scheiwiller-Garzanti) had published together: prayers, meditations, pedagogical pieces, occasional verses.
Keywords: Clemente Rebora; poetry; poet; complete works; collection; Vanni Scheiwiller; Garzanti; Meridiani Mondadori; phiolology; author's will